Thinking About (and With) the Prioress’s Tale: From Medieval Alterity to Modern Hate Narrative - Winstead, Karen A. (The Chaucer review, 2024)
Through a retrospective on teaching an upper-level Chaucer course in 2018, the author identifies the Prioress’s Tale as what she terms "hate narrative," a literary genre with distinct conventions that persists to our own day and has been deployed against marginalized groups, including racial, ethnic, and sexual minorities, refugees, and immigrants.